2017
DOI: 10.1002/pssb.201700234
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Nickel Catalyst Morphology on Layer‐Exchange‐Based Carbon Crystallisation of Ni/a‐C Bilayers

Abstract: Metal‐induced crystallisation with layer exchange is applied on Ni/C bilayer stacks deposited by three PVD techniques on SiO2. The layer stacks were deposited at room temperature by either ion beam sputtering, direct current magnetron sputtering or high‐power impulse magnetron sputtering. The influence of the Ni morphology on the layer exchange degree αLE and the resulting graphitic ordering is studied by atomic force microscopy, Rutherford backscattering spectrometry and Raman spectroscopy. The initial RMS ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Similar to the single-step graphene synthesis case, observed results can be explained by competition between the effects of the increased grain size [22] and increased Co surface roughness [36]. The possible additional dissociation of the C-H bonds by Co interlayer results in prevailing the boundary defects alone in graphene synthesized on silicon, as is seen in Figure 6e.…”
Section: Thickness Of Co Layersupporting
confidence: 60%
See 3 more Smart Citations
“…Similar to the single-step graphene synthesis case, observed results can be explained by competition between the effects of the increased grain size [22] and increased Co surface roughness [36]. The possible additional dissociation of the C-H bonds by Co interlayer results in prevailing the boundary defects alone in graphene synthesized on silicon, as is seen in Figure 6e.…”
Section: Thickness Of Co Layersupporting
confidence: 60%
“…In the case of the graphene synthesized on SiO 2 by annealing of the amorphous carbon and catalytic metal (Co or Ni) bilayer, the I 2D /I G ratio in all cases was lower than in the case of the graphene synthesized on quartz using PECVD and sacrificial Ni catalytic interlayer (see [7,[9][10][11]18,36], respectively). At the same time, the defects density in graphene synthesized by bilayer annealing in almost all cases was higher ( [7,[9][10][11]18,36]).…”
Section: Single-step Versus Two-step Graphene Synthesismentioning
confidence: 79%
See 2 more Smart Citations
“…Other recent papers dealt with Ni-enhanced graphitization of amorphous carbon films (a-C) prepared by CVD. The a-C/Ni films were annealed mainly in a hydrogen atmosphere. It was observed that carbon film exchanges with Ni film and graphitizes at elevated temperature. Recent theoretical studies explained the graphitization mechanism for RTA: a-C to graphene transformation entails the metal-induced crystallization and layer exchange mechanism. Carbon dissolution in Ni was excluded …”
Section: Introductionmentioning
confidence: 99%